Locating a Hub Port in Eastern Indonesia Using Network Analytics - Armand Omar Moeis; Nur Faqih Wirawan; Arry Rahmawan Destyanto; Andri D. Setiawan; Bahy Helmi Hartoyo Putra; Teuku Yuri Zagloel; Akhmad Hidayatno (Puslitbang Transportasi Laut, Sungai, Danau, dan Penyeberangan, 2022)
The main, current challenge to the maritime logistics system of Indonesia is the low level of freight transport from its eastern region. The transportation of goods to and from the eastern and western regions of Indonesia must be balanced if efficiency is to be enhanced and costs are to be reduced. One remedy to the current imbalance is increasing the existing economies of scale. This could be achieved by developing a hub port to enable goods to be consolidated and transported efficiently. The present study employs network analytics to determine the best site for a hub port in the eastern region of Indonesia. The coordinates of the ports in that region were analyzed using centrality algorithms and the NetworkX library. Based on analysis result, in perspective of relative distance between ports then Bitung port will be recommended as hub port in eastern Indonesia.